Shot put with lighter implements - Grammaticos, B. (New Studies in Athletics, 2014)
ABSTRACT Following a competition in 2012, a group of the world's top shot putters were invited to compete using a 5kg implement. The results were somewhat surprising in that the distances achieved were not as long as might be expected, based on the assumption that the length of a throw is inversely proportional to the mass of the shot. The aim of this paper is to provide an intuitive, physics-based interpretation of the results of the aforementioned competition and set a frame for the description of shot putting with implements of non-standard weights. The model, combined with the classical kinematics results for a projectile motion under the influence of gravity (and neglecting air resistance), allows the derivation of a simple expression for the dependence of the length of throw on the implement mass. This result is compared to existing performances and the limitations of the model when too heavy or too light implements are used are discussed. It is hoped that the results can assist coaches by providing a tool for interpreting the capability of athletes based on their results with different weight shots.